Boron analogue of vinylidene dication supported by phosphines - Lu, Wei (2020)
In the presence of a catalytic amount of heavier tetrylene dichlorides, an allenic diborene 1 undergoes a 1,3-hydrogen shift to afford a terminal diborene 2, which can be deemed a boron analogue of vinylidene dication stabilized by Lewis bases. X-ray diffraction analysis and computational studies revealed that 2 involves a conjugative interaction between the C═C and B═B π-orbitals. The reaction of 2 with ZnBr2 afforded the corresponding isolable complex 3, in which two boon centers coordinate to the Zn atom asymmetrically.